Asymmetric PdPtCu mesoporous hemispheres on nitrogen-functionalized graphene for methanol oxidation electrocatalysis. Issue 31 (15th January 2020) - Sun, Lizhi; Lv, Hao; Xu, Dongdong; Liu, Ben
Abstract : This work reports an easy solution-phase synthesis of asymmetric metallic mesoporous hemispheres on nitrogen-functionalized graphene for fuel cell electrooxidation. Abstract : Mesoporous metallic nanospheres with an asymmetric nanostructure and radially open nanochannels are of significant importance for application in nanoencapsulation and highly efficient mass transport nanosystems. Herein, we develop a facile approach that can produce asymmetric multimetallic mesoporous hemispheres (MHSs) by using amphiphilic dioctadecyldimethylammonium chloride as a mesopore-forming surfactant and nitrogen-functionalized graphene as a symmetry-breaking support. The final products display homogeneously alloyed elemental compositions (Pd, Pt, and Cu), unique asymmetric hemispherical nanostructures (∼95 × 43 nm), and cylindrically and radially open mesochannels (∼3.2 nm). These asymmetric multimetallic MHSs thus exhibit synergistic compositional and structural advantages such as an enlarged electrochemically active surface area, accelerated electron transfer and mass transport, and optimized CO anti-poisoning ability. When employed as an electrocatalyst for the methanol oxidation reaction, asymmetric PdPtCu MHSs exhibit a very high mass activity of 3.01 A mgNM −1 with a low activation energy of 24.9 kJ mol −1 . More importantly, the synergetic advantages of asymmetric PdPtCu MHSs also improve the electrocatalytic performance toward the electrooxidation of other organic fuels, including formic acid, ethanol, glucose, and glycerin. The findings demonstrated here offer an alternative strategy for the preparation of asymmetric metallic nanostructures that desirably function in fuel cell electrocatalysis.